Contemporary methods and technological advancements for evaluating the swiftness and precision of thrusts in swordsmanship - Britskiy V.A.; Aikin V.A. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to create a technological tool for training and assessment, the «Electronic-mechanical fencing target», and to demonstrate its effectiveness in evaluating the swiftness and precision of sword-based thrusts. Methods and structure of the study. The goal of the proposed invention is to monitor and assess the speed and precision of sword thrusts during training. To assess the impact of incorporating the developed simulator into the training regimen, a pedagogical experiment was conducted. The experiment aimed to verify our hypothesis that the «electronic-mechanical fencing target» enhances and improves the speed, strength, and coordination of fencers. The experiment was conducted among athletes aged 12, during the competitive period, and the experimental group was instructed to incorporate «Electronic-mechanical fencing targets» into their specialized training. Results and conclusions. The implementation of the «fencing, electronic-mechanical target» and the conducted trial demonstrated a significant improvement in the performance of the experimental group, particularly in terms of accuracy and errors across all exercises. There was no substantial increase in the performance of the control group. Overall, the experimental group outperformed the control group, with the exception of certain metrics in specific exercises. The increasing technical difficulty of the movements is evident in the results achieved by both groups.